Analisis Perhitungan Harga Pokok Produksi dengan Metode Full Costing pada UD. Madu Asli Sumbawa - Witri Fibri Mulyana; Agus Wahyudi (STATERA: Jurnal Akuntansi dan Keuangan, 2022)
The calculation of the cost of production is important to note because of the increasing competition between micro, small and medium enterprises in producing quality producst at quite competitive prices. This research aims to determine the calculation off cost of production using full costing method at UD. Madu Asli sumbawa. The method used in this study is aqualitative method with a descriptive approach. Source of data use primary and secondary data collected using observation, interview, and documentation thecniques. In this study researches conducted data analysis by collecting, reductioning, and test the validity of the data so that conclusions could be drawn. The result showed that the cost of goods sold of price per unit of Rp 19.235 for 100ml bottles, Rp 26.335 for 150ml bottles, , Rp 33.385 for 200ml bottles, , Rp 40.435 for 250 ml bottles, Rp 78.235 for 500ml bottles, Rp 149.235 for 1 liter bottles.